Corellation Between Achievement Motivation and Entrepreneurial Leadership Quality: Meta Analysis - Nasution, Arman Hakim (IPTEK The Journal for Technology and Science, 2010)
This article presents a meta analysis of the experimental and survey literature that has examined the effect of achievement motivation, as a part of the big five personality factors, and entrepreneurial leadership quality. This quantitative study review 20 studies based on independent samples (N = 6209). Summary analysis is provided to support the hypothesis in which the achievement motivation has a correlation with entrepreneurial leadership quality on a fairness procedural. Result indicates that the achievement motivation influences the quality of entrepreneurial leadership in a significant value (rc = 0.26). This finding is relevant to all stakeholders (educators, governments, and parents) to make a better decision on the development of entrepreneurial leadership policies.